Marmaduke Pickthall: Islam and the Modern World - Nash, Geoffrey ca. 20./21. Jh. (Muslim minorities, 2017)
This new volume of essays marks eighty years since the death of Marmaduke Pickthall. His various roles as translator of the Qurʾan, traveller to the Near East, political journalist writing on behalf of Muslim Turkey, and creator of the Muslim novel are discussed. In later life Pickthall became a prominent member of the British Muslim community in London and Woking, co-worker with Muslims in the Indian subcontinent, supporter of the Khilafat movement, and editor of the journal Islamic Culture under the patronage of the Nizam of Hyderabad. Marmaduke Pickthall: Islam and the Modern World makes an important contribution to the field of Muslims in Europe in the first half of the twentieth century